ANALYSIS OF THE GESTALT APPROACH IN GROUP COUNSELING - Tiara Maiza Dianti; Netrawati (Literasi Nusantara, 2021)
This article discusses the analysis of the gestalt approach in group counseling using references from relevant literature studies, the gestalt approach has several main concepts of counseling that are specific, namely: (1) views about humans, (2) orientation to life now and here, ( 3) awareness and responsibility, (4) contact, (5) unfinished business, (6) figure and ground. Gestalt counseling aims to help individuals have an understanding and awareness of their feelings, thoughts, actions, and experiences, their environmental situation and their position in that environment so that they have a sense of responsibility for themselves and their environment.